Exclusion of ferrochelatase gene mutations in patients with seasonal palmoplantar keratoderma - Schimmel, R J; Van TuylL Van Serooskerke, A M; Bladergroen, R S; Van Steensel, A M; Van Geel, M; Pasmans, S G M A; Frank, J (Cellular and Molecular Biology, 2009)
Erythropoietic protoporphyria (EPP) is an autosomal dominant disorder that results from a deficiency of ferrochelatase (FECH), the last enzyme in the heme biosynthetic pathway. The characteristic clinical symptoms usually manifest in early childhood on the sun-exposed areas of the body. They are due to protoporphyrin-induced photosensitivity and include pain, burning and stinging of the skin, followed by erythema and edema. Recently, the occurrence of predominantly seasonal palmar and palmoplantar keratoderma in patients with homozygous mutations in the FECH gene has been reported. These data suggested that palmoplantar keratoderma might be a clinical sign of EPP. Palmoplantar keratodermas (PPKs) are a heterogeneous group of genetic skin diseases and include a seasonal variant, erythrokeratolysis hiemalis et estivalis (EH), also known as keratolytic winter erythema. Because the skin symptoms in the latter disorder are similar to those reported for recessive EPP we examined the FECH gene in three unrelated Dutch Caucasian patients with a previous diagnosis of EH in whom mutations in several other genes had been excluded. However, sequencing analysis of the entire coding regions and the adjacent splice sites of the FECH gene in these individuals revealed absence of mutations. Hence, our data largely exclude the possibility that FECH mutations might be responsible for the palmoplantar skin phenotype observed in EH.